Development of soft skills in education with educational coaching - Lucero Baldevenites, Elisabeth Viviana; Lucero, Sonia Ivone; Gayol González, Ana María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
We often hear about the importance of soft skills in education and in the world of work. It would be essential for education at all levels to consider a paradigm shift, and to include them in study plans, giving them the same value and rigor as hard skills. It would be convenient for students to develop them in order to prepare them in the workplace and their transit in this increasingly changing world. Educational Coaching allows developing these skills in students, a change of observer, a different way of being and doing.